Designing The Balanced Scorecard for The Faculty of Economics of Satya Wacana Christian University - Haryanto, Jony Oktavian (Jurnal Widya Manajemen & Akuntansi, 2003)
Concerning the competition of universities in Indonesia, a research about the measurement and quality control from strategic perspectives will pose an interesting subject to be explored. The high-pressure of the economic condition, the unstable political environment, the globalization era as well as the unfair competition has changed the business environment. As a result, performance measures are used to guide the managers' decision and to evaluate the performance of managers and their units. This measurement is used as guidelines and incentives to facilitate the coordination among managers and business unit goals with those of the overall corporate goals. Without the performance measurement system, companies will probably move to a wrong decision. One of the tools that can provide comprehensive, coherent and balance performance measures is Balance Scorecard. Balance Scorecard does not only provide comprehensive measures( financial, Customer, Internal Business Process, and Learning & Growth), but is also provide a road map about how to achieve financial objectives without sacrificing long term performance. The Faculty of Economics of Satya Wacana Christian University (F-E SWCU), as one of the private universities in Indonesia, must also formulate and implement strategies that will fit with the high turbulent business environment. To avoid a pitfall of financial performance, FE SWCU have to implement Balance Scorecard. The Balance Scorecard designed for FE SWCU consists of strategic objectives derived from company vision mission, outcome measures and performance driver measures, and targets as milestones to know achievement of strategic objectives of the company.